Digital Everyday Life as an Asset: Spiritual and Cultural Practices Among Retired Women in the Rewwin Residence Community - Ilaihi, Wahyu; Moh. Mufad, Agoes (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
In Indonesia, the lives of retired women and technology are often overlooked. They are a group that is vulnerable to the digital divide. This study explores the digital technology asset into the everyday lives of retired women living in the Rewwin Residence Community in Waru, Sidoarjo, Indonesia. This study aims to understand how digital devices and platforms support and enhance spiritual and cultural practices in this community. This study uses qualitative methodologies with the approach used in ABCD/Asset Base Community Development to find and utilize their assets. The findings highlight the digital assets’ sense of asset ownership, physical, social, and human assets, and the wealth of religious and spiritual content. Understanding asset ownership has bridged and facilitated access to religious content, strengthened and fostered a sense of togetherness and belonging among their community, and offers insights into how digital practices can complement and enrich traditional cultural and spiritual practices in their everyday life stages. This study contributes to a broader understanding of contemporary Indonesian society’s relationship between assets, technology, aging, and cultural sustainability.